India - Accelerating Growth and Development in the Lagging Regions of India - World Bank (Washington, DC, 2012)
Although the Indian economy has been growing at a stellar rate of about 6 percent per annum since the mid-1980s, this achievement has been clouded by growing inequality and divergence in development outcomes among India's different regions. This study, thus, identifies a regional development strategy built around policies that are good for both the development of the Low Income States (LIS) and for India's overall development. That is, these policies are more in the nature of win-win rather than trade-offs between regional and national development. They focus on and address key issues: adverse neighbourhood effects; the comparative advantages of the LIS in agriculture and small town, agro-based, labor intensive industries; support for relatively inexpensive 'local or rural' infrastructure; critical human and social development that addresses exclusion, and; targeted investments of public expenditures alongside a build-up of capacity. These choices focus on core necessities rather than trade-offs between national and regional development. Further, they aim to achieve greater equity in welfare for the population of different regions rather than equality of economic activity in all regions. The rest of this summary discusses these findings in more detail. The next section, section B, presents the stylized facts about the lagging states; and finally, section C summarizes the findings on the constraints they face in raising growth and development.